A new synthesis strategy towards enhancing the structure and cycle stabilities of the LiNi0.80Co0.15Al0.05O2 cathode material. Issue 2 (12th December 2016) - Zhang, H. Z.; Liu, C.; Song, D. W.; Zhang, L. Q.; Bie, L. J.
Abstract : A new synthetic strategy (Al-compensation method) for LNCA cathodes is proposed in this paper. As a result, the obtained LNCA electrodes exhibit a more stable layered structure and enhanced electrochemical performances. Abstract : To enhance the structural stability and electrochemical performances of the LiNi0.80 Co0.15 Al0.05 O2 (LNCA) cathode material for Li-ion batteries, a new synthetic strategy (Al-compensation method) is proposed in this paper. The precursors Ni0.80 Co0.15 Al x (OH)0.95×2+3 x ( x ≤ 0.05) are prepared by a hydroxide co-precipitation method, and the final LNCA products are synthesized with the precursors and an additional (0.05 − x ) mole ratio of Al(OH)3 . This new strategy combines the advantages of co-precipitation and solid state reactions, avoiding the fast precipitation of Al 3+ and the flocculent precipitate. As a result, stoichiometric LNCA materials with uniform element distribution are obtained. Compared with LNCA samples prepared by conventional processes, the samples prepared by the Al-compensation method exhibit a better layered structure and hexagonal ordering, lower cation mixing and therefore higher coulombic efficiency and more stable cycle performance. Besides, the influences of calcination temperatures (650, 750 and 850 °C) on the structure and electrochemical performance of LNCA cathodes are investigated in advance, and the reasons for these influences are preliminarily discussed.